Combining 3D printing and screen-printing in miniaturized, disposable sensors with carbon paste electrodes. Issue 17 (20th April 2021) - Materon, Elsa Maria; Wong, Ademar; Gomes, Leonardo Mariano; Ibáñez-Redín, Gisela; Joshi, Nirav; Oliveira, Osvaldo N.; Faria, Ronaldo C.
Abstract : In this paper we report on a modular design that allows one to fabricate electrochemical sensors upon combining 3D printing and screen printing. Abstract : In this paper we report on a modular design that allows one to fabricate electrochemical sensors upon combining 3D printing and screen printing. The usefulness of the design is showcased with graphene paste electrodes (GPE) coated with magnetic microspheres used to detect the drug nimesulide (NIM), biomarkers dopamine (DOP) and uric acid (UA). Under optimized conditions, the limit of detection was 0.0023 μmol L −1 in the range from 0.5 to 9 μmol L −1, 0.01 μmol L −1 within the range from 0.8 to 6 μmol L −1, and 0.0034 μmol L −1 from 0.7 to 10 μmol L −1 for dopamine, nimesulide, and uric acid, respectively. The three analytes could also be detected in blood serum and artificial urine samples within approximately 20 s, which is promising for clinical applications. With the modular design, the paste can be prepared with a variety of nanomaterials, functionalized with biomolecules and magnetic particles, and then stored for later use. The working electrode may also be polished to allow for reuse. Furthermore, in contrast to standard sensors made with carbon pastes, the electrochemical sensor proposed here requires small volumes (20–200 μL), which is crucial for drug monitoring and other biomedical applications.